The nature of code - Shiffman, Daniel, ....-; Fry, Shannon, ....-; Marsh, Zannah, ....- ([United States] : D. Shiffman, 2012)
How can we capture the unpredictable evolutionary and emergent properties of nature in software? How can understanding the mathematical principles behind our physical world help us to create digital worlds? This book focuses on a range of programming strategies and techniques behind computer simulations of natural systems, from elementary concepts in mathematics and physics to more advanced algorithms that enable sophisticated visual results. Readers will progress from building a basic physics engine to creating intelligent moving objects and complex systems, setting the foundation for further experiments in generative design. Subjects covered include forces, trigonometry, fractals, cellular automata, self-organization, and genetic algorithms. The book's examples are written in Processing, an open-source language and development environment built on top of the Java programming language
"This work is licensed under the Creative Commons Attribution-NonCommercial 3.0 Unported License"--Page iii.
Includes bibliographical references and index.
Keywords: Computer programming; Computer simulation; Data processing; Databehandling; Datorsimulering; Programmering